Revisiting the Link Between Finance and Macroeconomic Volatility - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2013)
This paper examines the impact of financial depth on macroeconomic volatility using a dynamic panel analysis for 110 advanced and developing countries. We find that financial depth plays a significant role in dampening the volatility of output, consumption, and investment growth, but only up to a certain point. At very high levels, such as those observed in many advanced economies, financial depth amplifies consumption and investment volatility. We also find strong evidence that deeper financial systems serve as shock absorbers, mitigating the negative effects of real external shocks on macroeconomic volatility. This smoothing effect is particularly pronounced for consumption volatility in environments of high exposure - when trade and financial openness are high - suggesting significant gains from further financial deepening in developing countries.